The Role Of The Production Cost Budget As An Instrument For Planning and Controlling Production Costs In the Islamic Economics Perspective - Mayang, Mayang; Rifan, Dinda Fali (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
The purpose of this study is to determine the role of planning and controlling the production cost budget in terms of Islamic economics at Respiesusu Bandar Lampung. This study is qualitative and employs both primary and secondary data sources. The data was collected through interviews. The analysis technique employed was descriptive analysis, which is a means of describing or explaining facts connected to the discussion. In this case, the technique describes the analysis of Respiesusu's business planning and controlling production costs. The analysis yielded data on the production cost budget planning of Respiesusu Bandar Lampung from 2020 to 2021. The production cost budget plan was prepared according to the bottom-up theory and procedure, incorporating every line from bottom to top. However, the implementation of production costs did not meet the objective as planned, with a higher realization of 55.5% and 30.2% (unfavorable variance). In 2020, the difference in production cost deviation was greater than 5% in the uncontrolled deviation position, resulting in a suboptimal efficiency level of 155.67%. Furthermore, in 2021, production costs deviated by more than 5%, resulting in an unoptimized efficiency level of 128.56%. Jadi, anggaran biaya produksi pada UMKM Respiesusu belum berperan  secara optimal sebagai alat pengendalian biaya produksi. Thus, the production cost budget at Respiesusu MSMEs has not performed optimally in terms of cost control. Furthermore, Islamic economics advocates operating the economic system in line with Islamic economics' laws and core principles, one of which is honesty.